Back to the Present: How Not to Use Counterfactuals to Explain Causal Asymmetry - Fernandes, Alison (My University, 2022)
A plausible thought is that we should evaluate counterfactuals in the actual world by holding the present ‘fixed’; the state of the counterfactual world at the time of the antecedent, outside the area of the antecedent, is required to match that of the actual world. When used to evaluate counterfactuals in the actual world, this requirement may produce reasonable results. However, the requirement is deeply problematic when used in the context of explaining causal asymmetry (why causes come before their effects). The requirement plays a crucial role in certain statistical mechanical explanations of the temporal asymmetry of causation. I will use a case of backwards time travel to show how the requirement enforces certain features of counterfactual structure a priori. For this reason, the requirement cannot be part of a completely general method of evaluating counterfactuals. More importantly, the way the requirement enforces features of counterfactual structure prevents counterfactual structure being derived from more fundamental physical structure—as explanations of causal asymmetry demand. Therefore, the requirement cannot be used when explaining causal asymmetry. To explain causal asymmetry, we need more temporally neutral methods for evaluating counterfactuals—those that produce the right results in cases involving backwards time travel, as well as in the actual world.
PUBLISHED
Keywords: Loewer; Present; Counterfactuals; Causal asymmetry; Time travel; Causation; TIME